Reevaluation of AATCC Test Method 66: Dynamic Measurement of Wrinkle Recovery. Issue 1 (January 2015) - Junfeng, Tan; Lei, Wang; Jianli, Liu
AATCC Test Method (TM) 66 is a widely used method to determine wrinkle recovery of woven fabrics. Using a dynamic measurement system designed in the author's laboratory, this study enabled dynamic measurement of every frame image collected during the wrinkle recovery process. The precision of this system was tested against a standard wrinkle recovery angle tester. Data and plot comparisons indicated that the wrinkle recovery period in AATCC TM 66 should be shortened to balance both efficacy and efficiency.